Lithium and Valproate Levels Do Not Correlate with Ketamine’s Antidepressant Efficacy in Treatment-Resistant Bipolar Depression - Annie J. Xu; Mark J. Niciu; Nancy B. Lundin; David A. Luckenbaugh; Dawn F. Ionescu; Erica M. Richards; Jennifer L. Vande Voort; Elizabeth D. Ballard; Nancy E. Brutsche; Rodrigo Machado-Vieira; Carlos A. Zarate (Neural Plasticity)
Ketamine and lithium both inhibit glycogen synthase kinase 3. In addition, lithium and ketamine have synergistic antidepressant-like effects at individually subeffective doses in rodents. We hypothesized that ketamine’s antidepressant effects would be improved by therapeutic doses of lithium versus valproate and that serum lithium levels would positively correlate with ketamine’s antidepressant efficacy. Thirty-six patients with treatment-resistant bipolar depression maintained on therapeutic-dose lithium (n=23, 0.79 ± 0.15 mEq/L) or valproate (n=13, 79.6 ± 12.4 mg/mL) received 0.5 mg/kg ketamine infusion in a randomized, double-blind, placebo-controlled, crossover trial. The primary depression outcome measure—the Montgomery-Åsberg Depression Rating Scale (MADRS)—was assessed before infusion and at numerous postinfusion time points. Both lithium (F1,118 = 152.08, p<0.001, and d=2.27) and valproate (F1,128 = 20.12, p<0.001, and d=0.79) significantly improved depressive symptoms, but no statistically significant difference was observed between mood stabilizer groups (F1,28 = 2.51, p=0.12, and d=0.60). Serum lithium and valproate levels did not correlate with ketamine’s antidepressant efficacy. Although the study was potentially underpowered, our results suggest that lithium may not potentiate ketamine’s antidepressant efficacy in treatment-resistant bipolar depression.